Fighting disinformation and the subject's social protagonism: interrelation between Stuart Hall's Cultural Studies and Media and Information Literacy - Dos Santos, Camila Araújo [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2023)
Objective: Tracing a dialogical field between the precepts of Stuart Hall's Cultural Studies and the principles of Media and Information Literacy as a proposal for the creation of an interrogation space about the veracity of information and media content, in which the subject is centralized as protagonist in the process of critical reflection in the fight against disinformation. Methods: Uses theoretical-critical research that addresses the precepts of Cultural Studies and Media and Information Literacy in the fight against misinformation. It was constituted from articles and books from the scientific literature in Information Science and Cultural Studies. Based on the conceptual framework on culture, language, representation and meaning by Stuart Hall (1997, 2016), we seek dialogue with Media and Information Literacy in order to understand how the themes, when integrated and discussed, provide critical support to the subject in combating disinformation. Results: Based on the theory of Cultural Studies and the principles of Media and Information Literacy, we created a space for interrogating information and media content, in a metacognitive perspective, which serves as critical media informational references in promoting the subject's protagonism in the media combating disinformation. Conclusions: The dialogical articulation between Stuart Hall's Cultural Studies and Media and Information Literacy made us understand the need to operate forceful actions in the fight against disinformation, since the power structures struggle to appropriate the symbolic sociocultural representations of subjects to achieve their goals.
COMBATE À DESINFORMAÇÃO E O PROTAGONISMO SOCIAL DO SUJEITO: INTER-RELAÇÃO ENTRE OS ESTUDOS CULTURAIS DE STUART HALL E A COMPETÊNCIA EM INFORMAÇÃO E EM MÍDIA
Keywords: Cultural Studies; Disinformation; Media and Information Literacy; Protagonism